2017
DOI: 10.1016/j.actbio.2017.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Strontium and magnesium ions released from bioactive titanium metal promote early bone bonding in a rabbit implant model

Abstract: Implantation into osteoporotic bone constitutes a challenging problem because of early migration or loosening of the implant, which is primarily due to insufficient initial fixation in porotic bone. Therefore, it is desirable to provide implants with a capacity for early bone bonding. We have achieved conferring early bone bonding ability to titanium metal by releasing strontium ions or magnesium ions. Our treatment is promising for clinical applications to achieve early bone bonding of orthopedic or dental Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 42 publications
5
41
0
1
Order By: Relevance
“…The resultant Ti metal and its alloys slowly release these ions in the body environment so as to promote bone growth or exhibit antibacterial effect. These effects have been confirmed in animal experiments …”
Section: The Search For Novel Bone‐bonding Materials Using Sbfsupporting
confidence: 64%
See 1 more Smart Citation
“…The resultant Ti metal and its alloys slowly release these ions in the body environment so as to promote bone growth or exhibit antibacterial effect. These effects have been confirmed in animal experiments …”
Section: The Search For Novel Bone‐bonding Materials Using Sbfsupporting
confidence: 64%
“…These effects have been confirmed in animal experiments. 60 It is evident from these results that various kinds of novel bioactive materials with different functions can be obtained using SBF.…”
Section: Surface Modification Of Ti Metal For Enhanced Apatite Formationmentioning
confidence: 92%
“…As a result, the Ti with the Sr-containing calcium titanate was shown to markedly increase the cell viability after 3 days compared with the untreated Ti. This is consistent with our previous report in which the cell viability in the Ti subjected to the same treatment was significantly increased compared with untreated Ti on 5 days [45]. A similar increase in cell viability was observed in the case of Ti with 0.2% Ag at 1 and 3 days.…”
Section: Discussionsupporting
confidence: 92%
“…When primary mouse bone marrow stromal cells were cultured on the metal surface, increased cell activity including cell attachment, spreading, gene expression, and ALP activity was shown [30]. Yamaguchi et al [29] and Okuzu et al [45] reported that Ti having Sr-containing calcium titanate on its surface increased proliferation and osteogenic differentiation of MC3T3-E1 cells by releasing 0.92 ppm of Sr 2+ ions. In their reports, various types of gene expression, including integrin β1, β catenin, cyclin D1 and ALP were up-regulated and resulted in extracellular mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, of the excellent mechanical strength, toughness and anti-fatigue performance, metal scaffolds have been widely used in tissue engineering. For example, these metal materials have be used to repair or replace the lesioned or partly worn teeth [32], bones [33], joints or other tissues. These materials can also be regarded as cardiovascular stents [34,35], artificial heart valve [36], etc.…”
Section: Metal Scaffoldsmentioning
confidence: 99%